الإمام عبد الرحمن بن القاضي المغربي جهوده و اختيارته في علوم القراءات - دادة, سيرين (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2019)
خلاصة كان المغرب العربي معروفًا بشكل خاص بالمغرب المتطرف ، بميلهم نحو مجال القرآن وعلومه. ولا سيما القراءات والرسم و تعديل الرسم ، والذي استغرق جزءًا كبيرًا من السرد والإتقان. بالإضافة إلى هؤلاء صنف الناس تصنيفات رائعة وأعمال مكتوبة ثمينة بإتقان عالٍ و حد الكمال. ومن بين هؤلاء العظماء في المغرب الإمام سيدي عبد الرحمن بن القاضي المكناسي المغربي الذي عُرف بداني والجباري عصره. عاش الإمام حياة علمية مليئة بالحنان والكتابة. درس المدارس الأندلسية والمغربية. كان محاطًا بطلاب المعرفة و أثرى المكتبة القرآنية بأعماله القيمة وسمعته في جميع أنحاء المغرب. يأتي هذا البحث لتسليط الضوء على جانب مشرق من حياة الإمام الشخصية والعلمية وإظهار جهوده الكبيرة في علم القراءات سواء أدركت أم لا تزال محبوسة في خزائن المخطوطات. وكذلك كشف فضائل الأمة الإسلامية. علاوة على ذلك ، هذا يمثل البحث جمع ودراسة اختياراته المتعلقة بهذا العلم موضحًا ماذا تم في ارض فاس والمغرب Abstract The Arab Maghreb was known especially the Extreme Maghreb, by their tendency towards the field of the Qur'an and its sciences; particularly the readings, drawing, and drawing adjustment, which took a huge portion of narration and mastery. In addition, those people categorized great classifications and precious written works with high mastery and perfection. Among these remarkable people of Morocco was Imam Sidi Abdel Rahman bin al-Qadi al-Meknassi the Moroccan, who was known as Daniy and Jaabary his era. The Imam lived a scientific life full of tenderness and writing. He studied the Andalusian and Moroccan schools. He was surrounded by students of knowledge and enriched the Qur'anic library with his valuable works and his reputation throughout Morocco. This research comes to highlight a bright aspect of Imam's personal and scientific life and show his great efforts in the science of readings whether realized or still locked in the coffers of manuscripts; as well as reveal the virtues of the Islamic nation. Moreover, this research represents collection and study of its choices related to this science indicating what has been done in the land of fez and Morocco
أطروحة دكتوراه تخصص التفسير والتشريع المقارن في العلوم الاسلامية
Keywords: ا/اختيارات الامام في علوم القراءات/ عصر الامام ابن القاضي/جهود قراءات الامام ابن القاضي; A / Imam's Choices in the Sciences of Recitations / The Era of Imam Ibn Al-Qadi / The Efforts of Imam Ibn Al-Qadi's Readings